AYAT AL-QUR'AN TENTANG ISTILAH MANAJEMEN PENDIDIKAN ISLAM DAN PENERAPAN DALAM METODE KELEMBAGAAN - Supian, Sopwan (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2023)
Management is a very important thing to enable people to achieve goals. Because so much importance that the expert or experts trying to find methods, systems and theories to achieve the goal that was born of management as a science. Actually, the management was already there when man was created and can not be separated from everyday human life in arranging his life. As for the guidance and management of reference in Islam is to hold fast to the Qur'an and Hadith as the basic source of Islamic teachings that became a reference in solving the problems of Muslims, for all matters relating to human life and all its activities including the management of all items listed in affirmed in the Qur'an and the hadith of the Prophet Muhammad. In this paper will be studied management in the Islamic view (perspective of Qur'an and Hadith) which contains the notion of management, management functions (planning, organizing, Actuating and Controlling) and to discuss leadership skills and competencies on what to have for a leader which are all linked in the view of the Qur'an and Hadith.